Cooking at home : or, How I learned to stop worrying about recipes (and love my microwave) - Chang, David, 1977-; Krishna, Priya, 1991- (Clarkson Potter/Publishers, 2021)
"The globally renowned chef of Momofuku, star of Netflix's Ugly Delicious, and bestselling author of Eat a Peach now shares the kitchen hacks and culinary tricks he uses as a new home cook for a growing family--and shows the rest of us how to make the most of our cooking skills. Being a chef can make you the absolute worst kind of home cook. Either you're too fussy when dinner just needs to be on the table (without an hour of dishes to do afterwards), or, like Momofuku chef David Chang, you just never cook at home--your apartment is a place to sleep. But now, with a young family to feed, David finds himself having to retrain every instinct in his kitchen. With a decidedly non-restaurant pantry and no-frills equipment, he now has the same goals as every other mortal home cook: to make something as delicious as possible, in the least amount of time possible, with as little mess as possible. And what David learned is to never cook like a chef. Don't look at recipes. Choose frozen peas over fresh. Put the microwave to use--a lot. And go ahead, make the sauce for pasta cacio e pepe in a blender, no matter what that cool chef says. This is a book of delicious recipes that maximize flavor while minimizing effort and culinary orthodoxy. Rather than outlining formal recipes, David talks through how he tackles a dish step by step, starting with a basic template and then turning to endless variations. You might start with chicken thighs cooked with onion and garlic, but from there you can make coconut chicken curry or gochujang chicken and potatoes. You'll get a lazier version of Momofuku's ginger-scallion noodles, but then see how David riffs on it with a pesto-ish ginger-basil sauce. This cookbook is David's guide to unlocking culinary dark arts of shortcuts and hacks, brought to you by a chef who's made a career of doing everything the hard way...and is as tired of doing it as you are of hearing about it"--